Once Upon a Christmas Cheery in the Lab of Shakhashiri - Shakhashiri, Bassam Z. (1993)
One of many in a series of annual Christmas lectures given by Bassam Z. Shakhashiri, a Lebanese chemistry educator who spent most of his career at the University of Wisconsin-Madison. The 1993 lecture includes the combustibility of different elements and chemicals, experiments with solid state carbon dioxide, liquid nitrogen, acid and bases, and appearances by Bucky, the UW mascot; Santa Claus; and UW Chemistry professors Glenn E. Dirreen and Fred Juergens. This video was taken from a DVD, which itself was made from an unknown magnetic tape. Any distortions in the image and sound of the video are inherent in the DVD itself.
Keywords: Science--Study and teaching; Lectures; Chemistry--Experiments; University of Wisconsin--Madison; Christmas; Combustion; Liquid nitrogen; Carbon dioxide; Sublimation (Chemistry); Santa Claus (Fictitious character)